Synthesis, Characterization, and Pharmacological Evaluation of Selected Aromatic Amines. (15th February 2015) - Ismail, Hammad; Mirza, Bushra; Haq, Ihsan-ul; Shabbir, Muhammad; Akhter, Zareen; Basharat, Amina
Abstract : Aromatic amines 1-amino-4-phenoxybenzene (A-1A), 2-(4-aminophenoxy) naphthalene (A-2A), and 1-(4-aminophenoxy) naphthalene (A-3A) were synthesized by the reduction of corresponding nitroaromatics with hydrazine monohydrate and Pd/C 5% (w/w). The newly synthesized compounds were characterized by FTIR, 1 H NMR, 13 C NMR, UV-visible spectrophotometer, and mass spectrometry and their biological activities were investigated along with structurally similar 4-(4-aminophenyloxy) biphenyl (A-A). Results of brine shrimp cytotoxicity assay showed that almost all of the compounds had LD50 values <1 μ g/mL. The compounds also showed significant antitumor activity with IC50 values ranging from 67.45 to 12.2 µ gmL −1 . The cytotoxicity and antitumor studies correlate the results which suggests the anticancerous nature of compounds. During the interaction study of these compounds with DNA, all of the compounds showed hyperchromic effect indicating strong interaction through binding with the grooves of DNA. Moreover, A-3A also showed decrease inλ max confirming higher propensity for DNA groove binding. In DPPH free radical scavenging assay, all the compounds showed potential antioxidant capability. The compounds were highly active in protecting DNA against hydroxyl free radicals. DNA interaction and antioxidant results back up each other indicating that these compounds have potential to be used as cancer chemopreventive agents. Additionally, one compound (A-1A) showed significant antibacterial and antifungal activity as well.